Malaysian dental deans’ consensus on impact of COVID-19 and recommendations for sustaining quality dental education - Mohd-Dom, Tuti Ningseh; Lim, Kai Xin; Rani, Haslina; Yew, Hsu Zenn (Frontiers in Education, 2022)
The COVID-19 pandemic has significantly affected the training of dental students and the impact can be felt not just by the students but patients seen at dental school operated clinics. We used the modified-Delphi method to investigate the response from deans of all Malaysian dental schools on the impact of COVID-19, and to solicit their views on policy recommendations to sustain quality dental education during and beyond the infectious disease outbreak. Our analysis revealed that all dental deans are in agreement with strong consensus to ten out of fifteen items listed to be the challenges they faced due to the COVID-19 pandemic particularly these three items: “Patients under care of students experienced interrupted dental treatment which increases their risk of having their dental and overall well-being affected”; “Increased clinical budget for daily operations of students’ clinics to cater for extra PPE and related expenses”, and; “The students’ ability to meet clinical requirements for safe and competent practice”. All deans agreed with a strong consensus to the policy statements formulated based on the WHO’s Six Building Blocks to sustain quality dental education. In view of the results, we further discussed the importance of acknowledging that university-led dental clinics as an important part of the national healthcare system. Hence, we proposed that dental education need to have clear policies on having adequate number of trained staff, sufficient funds, information, supplies, transport, communications and overall guidance and direction to function. Having a National Dental Education Policy that addresses the unique challenges identified in this study will serve as a monumental cornerstone to sustain quality dental education during times of calamity.